Spatial analysis of mandibular condyles in patients with temporomandibular disorders and normal controls using cone beam computed tomography - Al-Rawi, Natheer Hashim; Uthman, Asmaa Tahseen; Sodeify, Sahar M. (European journal of dentistry, 2017)
ABSTRACT Objectives: The aim of the study is to investigate the condylar position and its relation to articular eminence and axial condylar angle in temporomandibular joint disorder (TMD) patients and in normal controls using cone beam computed tomography (CBCT). Materials and Methods: CBCT temporomandibular joint (TMJ) images of 70 participants (38 males and 32 females, mean age 26.4 years) were analyzed. They were divided into control group (including 35 subjects) and study group (including 35 subjects). Linear measurements of joint space and condyle determined the condylar position of each TMJ. Articular eminence height and inclination were also measured with axial condylar angle to determine its relation to condylar position. Independent and paired sample t -test was applied to compare between the groups and TMJ sides of the same group at significance level of 0.05. Results: Statistical significant differences were found between males and females of both groups regarding superior joint space (SJS), lateral joint space, A-P, and M-L condyle distance ( P < 0.05). SJS, medial joint space (MJS), and eminence angle were greater ( P < 0.01) in male's joints with TMD with flatter axial condylar angle ( P < 0.05), when compared with normal TMJ counterpart. Females TMJs showed significantly higher values of MJS of affected side when compared with normal counterpart with flatter axial condylar angle ( P < 0.05). Conclusion: Superior and MJS parameters were the ones that showed significant differences between affected and nonaffected joints. The mean axial condylar angle was smaller in joints with abnormal TMJ. This indicates that the condyles of the affected joints may rotate inward.